Unsur-Unsur Intrinsik dan Karaktetistik Sastra Anak Pada Cerita Terbentuknya Nama Lebong - Afifah, Aras Adzro; Anggraini, Dwi; Yuliantini, Nani (Universitas Bengkulu, 2024)
The research aims to describe the intrinsic aspects related to the theme, plot, setting, characters, and moral values in the story